Quality of life in cancer patients: a comparison of inpatient, outpatient, and rehabilitation settings - Hinz, Andreas; Weis, Joachim; Faller, Hermann; Brähler, Elmar; Härter, Martin; Keller, Monika; Schulz, Holger; Wegscheider, Karl; Koch, Uwe; Geue, Kristina; Götze, Heide; Mehnert, Anja (Supportive care in cancer, 2018)
PurposeThe aim of this study was to compare quality of life (QoL) data from cancer patients in different clinical settings with data from the general population.MethodsA sample of 4020 German cancer patients (1735 inpatients, 1324 outpatients, 961 participants in rehabilitation treatment) was tested with the EORTC QLQ-C30.ResultsCompared with the general population, cancer patients reported markedly worse QoL. There were clinically significant differences on all 15 scales of the EORTC QLQ-C30 (except one). For the sum score, averaging across 13 scales, the effect size of the difference between cancer patients and the general population was d = 1.16. Inpatients reported the greatest detriments to QoL, followed by the rehabilitation patients and the outpatients (mean sum scores 68.6, 71.0, and 72.3, respectively, compared with 89.2 in the general population). Mean scores for different groups of cancer sites are given separately for the three settings.ConclusionThe detriments to QoL were stronger than in comparable studies conducted on data from clinical trials. Since these detriments were found in all three settings to a similar degree, health care providers should offer their services not only to inpatients but to outpatients and patients treated in rehabilitation clinics as well. The data can be used for QoL comparisons of assessments from different settings.